Understanding gender relationships through sociodramatic experiences - Inês Gandolfo Conceição, Maria (2020)
Gender issues have produced interesting debates regarding the complementarity of the roles of post-modern woman and man, especially with regards to women entering the job-market and the social realm. This paper presents a study carried out at the graduate psychology course of Brasilia University. Through the use of action methods, the objective was to bring to the surface the feelings involved in the complex interaction between feminine and masculine roles, and to observe how cultural aspects and conserves manifest themselves in these roles. Sociodrama was used as a research method of intervention that aims to understand group processes and to offer mediation in problem situations, through the use of action and communication. Twenty-seven psychology students participated in this study, nineteen women and eight men. We looked at how gender roles complement each other in the socio-historical-politicalcultural context. The following were highlighted: discomfort caused by the psychological mirror that the dramatic scenes offered; discomfort of rational confrontation when discourse moved to concrete action; frustration for not being able to break the shackles of cultural conserves; aggression as the only reaction emerging when trying to conquer space within the social scene; and perplexity caused by the experience of being in the other’s skin.